Dialux - ett program för processdiagnostik i en embedded Linux miljö - Linder Saied, Robin; Eide, Emil (My University, 2019)
Embedded Linux is increasingly used in various products and systems. Despite this, there is a great lack of diagnostic programs for this type of system. The goal of this project is to start the development of a simple diagnostics program for a process that runs on embedded Linux. The work is carried out at Diadrom Systems AB, which is a specialist company with focus on autotech diagnostics. The work has been limited to monitoring a single process and presenting run values for CPU and RAM usage in a user-friendly format. The main questions that are dealt with are how to retrieve the necessary parameters, when should they be retrieved, how often reading should be done and how the data should be presented. A diagnostics program called Dialux was created with C / C ++ programming. This was done by developing three different iterations. A test program was also created to validate Dialux’s function. As a result, Dialux retrieves run values from the proc virtual file system. The most suitable built in test is the continuous built in test with the chosen time interval of two seconds. The data is presented in an Excel document.